Maternal Behavior and The Recurrence of Upper Respiratory Track Infection - Lukman La Bassy; Idham Soamole; Intan Soraya Leka (Humanistic Network for Science and Technology (HNST), 2018)
Acute respiratory tract infection is an acute infectious disease that attacks one or more parts of the respiratory tract from the nose (upper channel) to the alveoli (lower channel). According to acute respiratory infection (ARI) upper respiratory tract infection consists of three elements. They are infection, respiratory track and acute infection that is the entry of the microorganism in the body and incubate due to some symptoms. Acute infection is infection that occurred in 14 days. This research aims to describe the relationship between mother behavior (knowledge, attitude and action) with the recurrence of upper respiratory track infection. This research was an analytic survey research with cross sectional study method applying purposive sampling technique. The samples were 171 respondents. The research instrument was a questionnaire, then analyzed using Chi square test. It was concluded that there was a significant relationship between knowledge and the recurrence of ARI. Keywords: Knowledge, Attitude, Action, Acute respiratory tract infection